Perancangan Polybag Knockdown Dengan Material Polyethylene Terephthalate (PET) - Agus Kurniawan; Bayu Prabandono; Dicky Bondan Wirawan; Santoso Kalim (Universitas Muhammadiyah Yogyakarta, 2022)
During the Covid-19 pandemic, the need for food was one of the problems faced by the government. The government urges the public to do independent food planting using polybag planting media as one solution to overcome this problem. However, single-use polybags can increase the amount of plastic waste, which is still unresolved. This study aims to design the value of the knockdown polybag product and gain strength from the knockdown product design. Knockdown Polybag product design using the VDI 2222 method (Verein Deutscher Ingenieure / German Engineers Association). This method helps facilitate designing products and learning for beginners and can optimize the productivity of designers to find the most optimal and efficient problems. After determining the method used, the next step is planning, conceptualizing, designing, and completing knockdown polybag products. The result of the design concept from the VDI 2222 method is an alternative overall function (AFK) 2 which has a square cross-section, is cones-shaped to facilitate plant transfer applications on agricultural land, and uses a hook locking model, which is flexible, and easy to assemble and disassemble. The product design of knockdown polybags has been obtained to meet the needs according to those on the market. Therefore, knockdown polybags can be produced and used to make planting more accessible and reduce costs for farmers.